Improving Work Efficiency by Playful Work Design: Concepts and Creative Application in Organizations - Chuenphitthayavut, Krittipat (Journal of Behavioral Science for Development, 2023)
Successful work requires efficient and happy working together. Work design is one of the tools for work development that can help increase efficiency and create work satisfaction. Playful work design is a work design based on job enrichment approaches that focus on enjoying work. Employees can create a proactive, playful, and challenging work environment by designing play-like activities at work to perform for the fun and entertainment of the job. There are two important components, namely designing fun and designing competition, which are therefore important and indispensable to today’s work because playful work design helps reduce boredom and burnout conditions, making work efficient as the organization sets goals. The author therefore compiles concepts and theories related to playful work design, starting work design and work efficiency concepts, understanding the meaning, related concepts, and elements of playful work design, and their application in work, in order to be a guideline for further research and development in industrial and organizational psychology, behavioral science, and other related fields.